Convergent evolution of body color between sympatric freshwater fishes via different visual sensory evolution. Issue 11 (26th April 2019) - Montenegro, Javier; Mochida, Koji; Matsui, Kumi; Mokodongan, Daniel F.; Sumarto, Bayu K. A.; Lawelle, Sjamsu A.; Nofrianto, Andy B.; Hadiaty, Renny K.; Masengi, Kawilarang W. A.; Yong, Lengxob; Inomata, Nobuyuki; Irie, Takahiro; et al.
Abstract: Although there are many examples of color evolution potentially driven by sensory drive, only few studies have examined whether distinct species inhabiting the same environments evolve similar body colors via shared sensory mechanisms. In this study, we tested whether two sympatric freshwater fish taxa, halfbeaks of the genus Nomorhamphus and ricefishes of the genus Oryzias in Sulawesi Island, converge in both body color and visual sensitivity. After reconstructing the phylogeny separately for Nomorhamphus and Oryzias using transcriptome‐wide sequences, we demonstrated positive correlations of body redness between these two taxa across environments, even after phylogenetic corrections, which support convergent evolution. However, substantial differences were observed in the expression profiles of opsin genes in the eyes between Nomorhamphus and Oryzias . Particularly, the expression levels of the long wavelength‐sensitive genes were negatively correlated between the taxa, indicating that they have different visual sensitivities despite living in similar light environments. Thus, the convergence of body colorations between these two freshwater fish taxa was not accompanied by convergence in opsin sensitivities. This system presents a case in which body color convergence can occur between sympatric species via different mechanisms. Abstract : We tested whether body color convergence between two sympatric freshwater fish taxa, halfbeaks of the genus Nomorhamphus and ricefishes of the genus Oryzias, which co‐occur in a variety of habitat environments in Sulawesi Island, evolves by sensory drive. The expression profiles of opsin genes revealed that the convergence of body colorations between these two taxa cannot be explained simply by the sensory drive that occurs independently in both of them.